Analisis Rantai Pasokan (Supply Chain) Daging Sapi dari Rumah Pemotongan Hewan sampai Konsumen di Kota Surakarta - Syakur, Moh. Abdus; Purnomo, Sutrisno Hadi; Hertanto, Bayu Setya (Universitas Sebelas Maret (UNS), 2017)
This research aims to: (1) analyzing the products flow, financials flow and information flow on the beef supply chain, (2) analyze the level of efficiency in the marketing of beef supply chain, (3) analyze the value added in the process of cutting a beef cattle in Surakarta. This research was carried out in September – November 2016 in Surakarta. The methods used in this research is a survey method. Sampling method in this research is purposive sampling technique and snowball sampling. The analysis of the data used in this research is descriptive analysis, efficiency of marketing and value added analysis method with Hayami. The results of the analysis show that: (1) there are 3 streams in the beef supply chain in Surakarta there are: products flow, financial flow and information flow that goes with the optimal; (2) beef distribution channels in Surakarta is efficient based on the value of the marketing efficiency of 0,79%, margins of profitable marketing (Ski > Sbi) amounting to Rp 7,500 and shared value that is proportionate in accordance with the contribution given per link; and (3) the average value obtained is Rp 70.551, 18/kg or 59.8% of total output produced.